The role of nutrition and genetics as key determinants of the positive height trend - Grasgruber, P; Cacek, J; Kalina, T; Sebera, M (Economics and human biology, 2014)
The aim of this study was to identify the most important variables determining current differences in physical stature in Europe and some of its overseas offshoots such as Australia, New Zealand and USA. We collected data on the height of young men from 45 countries and compared them with long-term averages of food consumption from the FAOSTAT database, various development indicators compiled by the World Bank and the CIA World Factbook, and frequencies of several genetic markers. Our analysis demonstrates that the most important factor explaining current differences in stature among nations of European origin is the level of nutrition, especially the ratio between the intake of high-quality proteins from milk products, pork meat and fish, and low-quality proteins from wheat. Possible genetic factors such as the distribution of Y haplogroup I-M170, combined frequencies of Y haplogroups I-M170 and R1b-U106, or the phenotypic distribution of lactose tolerance emerge as comparably important, but the available data are more limited. Moderately significant positive correlations were also found with GDP per capita, health expenditure and partly with the level of urbanization that influences male stature in Western Europe. In contrast, male height correlated inversely with children's mortality and social inequality (Gini index). These results could inspire social and nutritional guidelines that would lead to the optimization of physical growth in children and maximization of the genetic potential, both at the individual and national level.
Keywords: běloši; Genetic Markers; GDP per capita; dieta; Nutritional Status; genotyp; Male; Child Mortality; Europe; Genetics; Genotype; Socioeconomic Factors; Nutrition; Male height; mužské pohlaví; Body Height; Adult; Guanosine Diphosphate; tělesné váhy a míry; guanosindifosfát; dítě; Child; socioekonomické faktory; dětská úmrtnost; Humans; Health Expenditures; celosvětové zdraví; výdaje na zdravotnictví; Global Health; White People; Diet; dospělí; nutriční stav; genetické markery; tělesná výška; lidé; Body Weights and Measures